The Blurring of Boundaries in Bioscientific Discourse - Tomašovičová, Jana (2021)
New technologies have revealed previously unknown and invisible parts of the human body and made it visible at the molecular level, revealing in turn more detailed structures and arrangements than those which were previously available. In doing so, in many ways they refine, expand, and even completely overturn forms of contemporary knowledge. This book maps the shifts and blurring of boundaries in contemporary bioscientific discourse. The authors of its chapters trace the shifts of boundaries in terms of the gradual blurring of the validity of established concepts, interpretive frameworks, and standards of judgment, which are analysed from ontological, gnoseological, ethical, and social perspectives. At the same time, they also map the blurring of boundaries in terms of the interdisciplinary crossing of boundaries between various scientific and artistic disciplines. The shifting of boundaries ultimately forms a part of these boundaries' definition; upon the basis of a rationally guided discussion, these shifts can be guided and corrected so as to avoid any irreversible damage. Jana Tomašovičová is a philosopher with a special interest in contemporary philosophy and bioethics. She analyses the impact of biotechnology on traditional social, ethical, and anthropological concepts and their relevance in new conditions. She is an associate professor at the Faculty of Arts, University of Ss. Cyril and Methodius in Trnava, Slovakia. During her bioethics research, she conducted short research stays at the universities of Bonn, Heidelberg, Tübingen, and Zürich.